Ayurvedic Response to COVID-19 Pandemic in Kerala, India and Its Impact on Quarantined Individuals - A Community Case Study - Sharmila Mary Joseph; Divya S. Iyer; Rajmohan Velayudhan Pillai (Frontiers Media S.A., 2021)
The SARS-CoV-2 infection has resulted in massive loss of valuable human lives, extensive destruction of livelihoods and financial crisis of unprecedented levels across the globe. Kerala, a province in India, like the rest of the country, launched preventive and control measures to mitigate the impact of COVID-19 early in 2020. The Government of Kerala started 1206 Ayur Raksha Clinics and associated Task Forces across the state in April 2020 to improve the reach and penetration of Ayurvedic preventive, therapeutic and convalescent care strategies for the COVID-19 pandemic. The implementation framework of the strategy was properly designed, and had a decentralized, people-centered, and participatory approach. Kerala has robust public health machinery with adequate human resource and infrastructure in the conventional medicine sector. This community case study examines how the decentralized organizational framework was effectively utilized for facilitating the delivery of Ayurvedic services in the COVID-19 situation. Key observations from the study are: Ayurvedic programs implemented systematically, under an organized framework with social participation enables wider utilization of the services. Such a framework is easily replicable even in resource-poor settings. Rather than a pluralistic approach, an integrative health system approach may be more viable in the Kerala scenario in public health emergencies.